2015
DOI: 10.14295/aohl.v21i2.485
|View full text |Cite
|
Sign up to set email alerts
|

Recipientes e substratos na germinação e desenvolvimento de crisântemo e amor-perfeito

Abstract: The aim of this work was to evaluate the substrate effect and recipient size on the germination and initial growth of chrysanthemum and perfect-love ornamental plants. The works was carried out in the Horticulture Nursery from UTFPR - Campus Dois Vizinhos - Paraná State, Brazil. The experimental design was in blocks randomized, in factorial 3 x 4 (recipient size x substrate), with four replications, considering 4 recipients by plot. It was used as recipients, small, medium and king container and as substrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(8 reference statements)
1
3
0
1
Order By: Relevance
“…Higher values of stem length were observed for Calabria, with average of 19.7 cm, similar to Sheena with 18.6 cm, and higher than variety Indianapolis, with 17.2 cm. Similar results were found by Mota et al (2007) and Pirola et al (2015) whom noticed increments in plant height when increasing the dosage of the applied treatment. This is due to the fact that these nutrients are involved in cell elongation and division, and also because they are fundamental constituents of organelles and compounds involved in photosynthesis, especially nitrogen, thus resulting in response of stem length (BARBOSA et al, 1999;RODRIGUES et al, 2008;CASTRO et al, 2011;BALDOTTO and BALDOTTO, 2015).…”
Section: Dry Matter Of Leaves Stems and Length Of Stemssupporting
confidence: 87%
See 1 more Smart Citation
“…Higher values of stem length were observed for Calabria, with average of 19.7 cm, similar to Sheena with 18.6 cm, and higher than variety Indianapolis, with 17.2 cm. Similar results were found by Mota et al (2007) and Pirola et al (2015) whom noticed increments in plant height when increasing the dosage of the applied treatment. This is due to the fact that these nutrients are involved in cell elongation and division, and also because they are fundamental constituents of organelles and compounds involved in photosynthesis, especially nitrogen, thus resulting in response of stem length (BARBOSA et al, 1999;RODRIGUES et al, 2008;CASTRO et al, 2011;BALDOTTO and BALDOTTO, 2015).…”
Section: Dry Matter Of Leaves Stems and Length Of Stemssupporting
confidence: 87%
“…Substrate temperature, light and fertilization are of paramount importance in quality and productivity of inflorescences (BACKES et al, 2004;PIROLA et al, 2015). The knowledge of nutritional needs of the crop has not only an important impact on quality, productivity and longevity of the inflorescences and plant but also on maximizing the ecosystem efficiency with minimum impact on environment avoiding eutrophication on rivers and lakes (MOTA et al, 2013;SCHWAB et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sousa et al (2011) em produção de zínia (Zinnia elegans (Jacq)) da família das Asteraceae em diferentes recipientes atingiu as melhores médias para a altura de 6,18 cm em recipiente com menor volume, contrário aos resultados encontrados no presente estudo em que os vasos de maior tamanho alcançaram a altura de 18,13 cm se sobressaindo em relação ao menor com 16,82 cm. Em estudos realizados por Pirola et al (2015) em crisântemo (Dendranthema grandiflora (Tzvelev)), observou-se os melhores resultados para a altura da planta em cultivo com vasos maiores. É importante ressaltar que a altura das plantas obtidas no presente ensaio para os dois tipos de vasos testados, estão dentro do padrão de comercialização do Veiling Holambra (Veiling Holambra, 2018).…”
Section: Resultsunclassified
“…Different genotypes, even those with more expressive growth, can be grown in pots, with their size monitored, in order to obtain a harmony of the plant, and even a better efficiency in the production of the aerial part (Pinto et al, 2010). Pirola et al (2015) reported that countless materials can be used as a container in the development of chrysanthemum and pansy, ornamental species of great importance in the market, demonstrating that each container has a different influence on the root development of plants, consequently providing the largest total length of the plants. plants Concerning these characteristics, the development of scientific work related to pot adaptation, more efficient cultivation techniques that can guarantee lower production costs, becomes important.…”
Section: Introductionmentioning
confidence: 99%